Conservation and Utilization: Community-Based Natural and Cultural Tourism Site Design in West Bali National Park - Muhamad; I Putu Gede Arya Kusdyana (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
The harmonious relationship between natural, social, and cultural landscapes for sustainable use represents an interaction between sites and surrounding communities. This research focuses on natural and cultural tourism allocations in forest resource management within the utilization zone of West Bali National Park (TNBB). Qualitative data analysis was conducted in the utilization zone designated for natural and cultural tourism, involving local communities around the conservation area. The findings indicate that the landscape in the utilization zone can maintain TNBB's conservation area sustainability through nature and culture-based tourism sites. This is supported by community involvement, which fosters harmonious relationships between TNBB management and village communities while improving local welfare through conservation efforts. The natural conditions and cultural aspects of six buffer villages directly bordering the National Park serve as powerful tourist attractions, contributing to the area's preservation and sustainable development.